2020
DOI: 10.1016/j.annonc.2020.04.073
|View full text |Cite
|
Sign up to set email alerts
|

O-20 Phase I/IB study of regorafenib and nivolumab in mismatch repair proficient advanced refractory colorectal cancer

Abstract: Background: Fluoropyrimidines are the cornerstone of chemotherapy in many solid tumors and linked to cardiotoxicity in about 5% (Polk, Cancer Treat Rev 2013), often leading to its discontinuation. Cardiotoxicity may be less common with the fluoropyrimidine S-1 and successful switch from other fluoropyrimidines has been reported (Kwakman, EJC 2017).Methods: This 6-country, 12-center, cohort study included patients with solid tumors (oesophageal, gastric, small bowel, colon, rectum, anal, gall ways, pancreas, br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Although toxicity was similar to the Japanese study REGONIVO, very modest efficacy was reported with no objective responses [122]. Intrinsic genetic differences between the Asian and the Caucasian populations have been suggested as an explanation for these heterogeneous results, though in the absence of a clear functional hypothesis [29].…”
Section: Anti-tams + Immune Checkpoint Inhibitorssupporting
confidence: 55%
“…Although toxicity was similar to the Japanese study REGONIVO, very modest efficacy was reported with no objective responses [122]. Intrinsic genetic differences between the Asian and the Caucasian populations have been suggested as an explanation for these heterogeneous results, though in the absence of a clear functional hypothesis [29].…”
Section: Anti-tams + Immune Checkpoint Inhibitorssupporting
confidence: 55%
“…However, in the phase II REGOMUNE trial (NCT03475953) of regorafenib plus an anti-PD-L1 IgG1 monoclonal antibody, avelumab, in the treatment of solid tumors, including 48 patients with pMMR/MSS mCRC, no objective response was noted, with a median PFS of 3.6 months in mCRC [41]. Furthermore, a phase I/IB trial of regorafenib plus nivolumab in 28 patients with refractory pMMR/MSS CRC showed similar results as the RE-GOMUNE trial, with an ORR of 5% and a median PFS of 4.3 months [42]. Thus, combination treatment with regorafenib and ICIs can result in modest clinical activity in patients with pMMR/MSS CRC.…”
Section: Anti-angiogenetic Inhibitorsmentioning
confidence: 84%
“…The safety profile of the combination was manageable, and 80 mg was selected as the recommended dose for regorafenib to use in phase II trials. Less promising data have recently been reported by the investigators of a phase I/IB trial conducted in US, where the combination of regorafenib and nivolumab yielded a response rate of 6% and a median PFS of 5.7 months in a population of chemorefractory colorectal cancer patients [13]. These inconsistent results have been largely attributed to the high proportion of patients with unfavourable prognostic features and negative predictive factors for immunotherapy (such as right-sided tumour location and liver metastases).…”
Section: Study Rationalementioning
confidence: 94%